Modeling of Agricultural Waste Higher Heating Value Based on Proximate Analysis. - CHETANGNY, Patrice Koffi; HOUEMENOU, Alexandre; ADAMON, David G. F.; ZOGBOCHI, Victor; HOUNDEDAKO, SOSSOU; FAGBEMI, LATIF ADÉNIYI; BARBIER, Gérald; VIANOU, Antoine; CHAMAGNE, Didier (My University, 2023)
A model of the higher heating value on a dry basis from the proximity analysis of agricultural wastes in Benin has been proposed in this article. This model was developed using agricultural residues such as shea shells and cakes, cotton and soybean stalks, corn cobs and peanut shells identified as part of the implementation of an experimental system. The validity of this model has been established for the Higher Heating Value (HHV) between 18.07 MJ/kg to 25.91 MJ/kg, Volatile Matter rate (%VM) 66.8% to 79.87%, Fixed Carbon rate 13.83% to 29.59%, and Ash content (%Ash) 3.47% to 6.3%. The model has an average absolute error of 2.79% and a bias error of 0.034%, significantly better than the most accurate literature prediction model, which offers a mean absolute error of 5.97% and –4.66% for the bias error. This work presents as well the first data from the proximity analysis of agricultural residues in Benin. These analyzes are carried out using a well-structured methodology that respects the standards and measures of simple random sampling forsample collection. Samples prepared under appropriate conditions are analyzed using standardized protocols for the agricultural wastes studied.
Keywords: Agricultural Wastes; Higher Heating Value; Prediction Model; Proximity Analysis